(untitled) (Global Journal of Human-Social Science, 2020)
Though the phenomenon of Counter-Globalization occurred recently economic globalization and regional economic integration are still the trends especially as shown by the Asian economic integration process The Asian regionalization is in very initial stage emerging in various cooperation mechanisms forming a multi-level pattern of coexistence in the later erupted advantage Based on the theories of regional economics and the Optimal Currency Zone within the 10 4 FTA considered frame inc The ASEAN China India Japan and South Korea an academic study is carried out comparing with the case of the European regionalization The research will focus on conditions and barriers in the Asian currency unification process and finally a corresponding step proposal to set up the ACU Experimental Zones together with a model is putting forward